La potencia de lo sagrado y la comunidad. Un rastreo de Durkheim a Bataille en el Colegio de sociología - Lorio, Natalia (2013)
“The power of the sacred and the community. A tracking from Durkheim to Bataille in the College of Sociology”. This paper studies the notion of sacredin Durkheim’s developments within the French sociological school and of those from Georges Bataille in the College of Sociology. Considering the peculiarity of these developments, which had influence in the early twentieth century, we show the broadening of the interpretation of the sacred to other phenomena different from religious issues, pointing the potential of this concept in the formulation of a critique of secular modernity. So, the sacred is the nodal point from which both Durkheim and Bataille, each one from his own perspective, problematizesthe social effervescence, where, also, community becomes a central problem, raising questions and issues in the realm of contemporary political thought.